Cuidados paliativos y su influencia en la calidad de vida en los pacientes atendidos en el Hospital de Solca-Loja. - Galvez T., Soledad E. (2013)
The task of the nurse in the care of terminally ill patients will be somewhat easier if you have a strong personal philosophy and objective fitness and positive to the disease. The nurse must be able to provide support and hope to patients and families. Interestingly, the concept of Hospice, ie where patients can be hospitalized for short or long periods to receive nursing care. These places try to maintain an environment similar to households, while helping to liberate families emotional and physical burdens that involves constant care. They also provide social, medical, and nursing, nutritional and psychological support to patients and their families so that the dying process is worthy. In this context the Hospital "Vicente Rodriguez Witt" of Loja Solca has been characterized for the care of patients who suffer from terminal illnesses, whose primary goal is to alleviate physical distress, mental and spiritual, which was determined in the present investigation , presenting the theme "PALLIATIVE CARE AND ITS INFLUENCE ON THE QUALITY OF LIFE IN PATIENTS TREATED IN HOSPITAL SOLCA-LOJA" with a descriptive; whose universe was constituted by 52 people: patients and nurses who work in that institution. To achieve the objectives and determine how they influence nursing palliative care in the quality of life of patients, the technique was used to interview each patient, and for different palliative care nurse implements, technique was applied of observation. Bringing it was determined that providing palliative care nurses in the chemotherapy service Solca Hospital Loja is very satisfactory because 100% of patients receive nursing care covering all real needs and as an individual's potential and improve their quality of life to be able to perform daily activities